Numerical study of the effect of infilling material in a hole-like flaw on acoustic emission characteristics and damage evolution in sandstone - Zhang, Qi; Ma, Chun-Chi; Jiang, Yalong; Geng, Huale (Frontiers in Earth Science, 2023)
Per-existing flaws are wide existence in rock mass, which have a significant effect on mechanical properties and fracturing behaviors. To investigate the effects of flaw type, infilling material, and flaw shape on the mechanical properties and fracture evolution of rock, a series of uniaxial compression tests were conducted on sandstone specimens. The bonded-particle model (BPM) and acoustic emission (AE) techniques were adopted to study the cracking process and AE characteristics of sandstone. The results indicate that relatively rigid infilling can significantly improve the mechanical properties of the rock. The AE simulation in the BPM revealed its fracture evolution, and there is a good consistency between fracture evolution and AE events. The cracking process and crack type around the hole-like flaw are influenced by the type of infilling material and its shape due to changes in the stress state around the hole-like flaw. Tensile cracks in nature usually initiate from the top or the bottom of a hole-like flaw. The shear and compaction cracks in nature prefer to initiate within the infilling material or from the lateral sides of the hole-like flaw. The cracking process of rocks can be characterized by the b-value, the variation of which is comparable with fracture behaviors and energy dissipation.